Application of modified fuzzy TOPSIS in optimising competency and strategic success. (7th June 2021) - Singh, Chandan Deep; Kaur, Harleen
The strategic success of an industry depends upon manufacturing competencies, that is, their competitive advantage. If the industry ensures better quality and is more reliable than its competitors, this will translate into increased sales, and the creation of a sound customer base for greater market share, thus returning with enhanced profit, growth, and expansion. Competitive priorities are the operating advantages that a firm's processes must possess in order to outperform its competitors. The operating advantage for the industry is assessed, evaluated, and measured with the help of the parameters of cost, quality, time, design, flexibility, etc. Firms have traditionally pursued these goals through the adoption of advanced technologies, and innovative manufacturing practices, such as concurrent engineering, JIT, and empowerment of workers. This paper suggests the use of modified fuzzy TOPSIS method for optimisation of strategic success and competency.